Examination of Flammable and Heat Protective Polymer Composite Coatings Using Oxygen Index Determination - DSc K. M. Murtazaev; H.G. Azimov (Research Parks Publishing LLC, 2023)
This article discusses the effect of fire-retardant expanded polymer coatings based on an acrylic copolymer on the oxygen index of polymer binders, flame retardants, gas-forming expanded-active chemical additives and fillers in a ratio of 5-42% at a temperature of 200-300 0C.